1997
DOI: 10.1071/a96157
|View full text |Cite
|
Sign up to set email alerts
|

Water use and drainage under phalaris, cocksfoot, and annual ryegrass pastures

Abstract: The water balance equation was used to calculate plant water use and drainage below a depth of 1·1 m for phalaris, cocksfoot, and annual ryegrass pastures and bare fallow at Rutherglen in north-eastern Victoria. Rainfall from 1990 to 1993 averaged 693 mm/year. Soil water use was greater under perennials over the summer{autumn period and the soil profile was approximately 50 mm drier at the beginning of each drainage season. Following autumn rains, soil water profiles under all treatments converged, usually rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…Armstrong et al (1999) showed that perennials were able to extract more water from the soil than the annual legumes and sorghum. Similarly, Ridley et al (1997) demonstrated the potential of lucerne grown in rotation with crops to reduce water losses to deep drainage compared with annual crops and pastures. …”
Section: Plant Adaptationmentioning
confidence: 99%
“…Armstrong et al (1999) showed that perennials were able to extract more water from the soil than the annual legumes and sorghum. Similarly, Ridley et al (1997) demonstrated the potential of lucerne grown in rotation with crops to reduce water losses to deep drainage compared with annual crops and pastures. …”
Section: Plant Adaptationmentioning
confidence: 99%
“…Phalaris transpired 130 mm more water (33% increase) and produced 17% more dry matter than annual pasture under a medium cutting height (Table 5). Similarly, in the study of Ridley et al (1997), the yield of phalaris + N treatment increased from around 8 t to more than 16 t/ha between 1992 and 1993, despite similar pan evaporation in both years and higher April-October rainfall in 1992 (580 mm) than in 1993 (368 mm). The increased yield was more likely due to increased soil fertility, as these pastures received 400 kg N in 1992 and 500 kg N in 1993.…”
Section: Wue and Implications For Soil Water Usementioning
confidence: 97%
“…Therefore, a 50% improvement in the net pasture production, say from 8 t to 12 t, through improved agronomic practices and/or use of higher yielding varieties would use approximately 160 mm more water, irrespective of the water lost through soil evaporation or evaporative demand. Studies by Ridley et al (1997) and Clifton and Taylor (1995) reported that increased yields through better agronomic management practices resulted in higher soil water use. Clifton and Taylor (1995) reported that swards of both phalaris (Phalaris aquatica) and cocksfoot (Dactylis glomerata) that were allowed to grow to higher herbage mass were able to transpire more water than swards that were kept short.…”
Section: Wue and Implications For Soil Water Usementioning
confidence: 99%
See 2 more Smart Citations